2013
DOI: 10.1634/theoncologist.2012-0427
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Older Patients With Head and Neck Cancer: A Review

Abstract: Learning Objectives Compare survival and toxicity outcomes of older patients with head and neck cancer with those of their younger cohorts. Describe the role played by comorbidity, quality of life, and supportive care in the treatment decision and treatment process of older patients with head and neck cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
134
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(141 citation statements)
references
References 94 publications
(77 reference statements)
5
134
1
1
Order By: Relevance
“…7,56 Taken together, these findings underscore the fact that older adults with cancer comprise an extraordinarily heterogeneous group of patients, made of a range of very fit to very frail individuals with disparate performance status, functional status, and comorbidity burden. In fact, a recent study from the National Cancer Data Base including patients diagnosed between 1998 and 2011 demonstrated that for patients aged 71 and older, there was improved survival with concomitant CRT in those aged 71 to 80 with low comorbidity scores, but not in those with multiple comorbidities or over the age of 80.…”
Section: Methodsmentioning
confidence: 82%
See 1 more Smart Citation
“…7,56 Taken together, these findings underscore the fact that older adults with cancer comprise an extraordinarily heterogeneous group of patients, made of a range of very fit to very frail individuals with disparate performance status, functional status, and comorbidity burden. In fact, a recent study from the National Cancer Data Base including patients diagnosed between 1998 and 2011 demonstrated that for patients aged 71 and older, there was improved survival with concomitant CRT in those aged 71 to 80 with low comorbidity scores, but not in those with multiple comorbidities or over the age of 80.…”
Section: Methodsmentioning
confidence: 82%
“…7 Moreover, given that the epidemiology of HNSCC in older patients has dramatically changed over the past decade, with rapid increases in oropharyngeal cancers, likely due to HPV-related malignancies, and concomitant decreased incidence of tobacco- and alcohol-related cancers arising from the oral cavity, larynx, and hypopharynx, 8 the limited data available may be less applicable to older patients seen in current practice. This evidence vacuum, combined with projected increases in absolute number of older patients with HNSCC, 9 creates a situation in which it is imperative to develop high level evidence to drive treatment paradigms for older patients.…”
Section: Introductionmentioning
confidence: 99%
“…We examined associations between multiple sociodemographic, clinical, symptom distress, and mood variables and neurocognitive performance, and few significant associations were noted. Although reflective of the changing demographic of HNC patients, the sample is relatively young and may not be representative of the classic HNC population which is older [44]. Neurocognitive function in older and younger HNC patients may differ.…”
Section: Limitationsmentioning
confidence: 99%
“…Curative treatment for locally advanced HNC often involves a combination of modalities, including surgery, radiation, and/or chemotherapy. 10 The optimal selection of patients for intensive treatment is not standardized and remains controversial. 7,8 Indeed, in clinical practice, many patients, especially older patients and those with significant comorbidities, may be treated with less intensive treatments such as cetuximab with radiation 9 and radiation therapy alone or even no treatment.…”
Section: Introductionmentioning
confidence: 99%